ENTRENCHMENT OF ETHICS, TRANSPARENCE AND RESPONSIBILITY THROUGH THE APPLICATION OF ICTS IN ORGANISATIONS IN RIVERS STATE - Bestman, Anthonia Enefaa (Acta Scientiae et Intellectus, 2024)
The study examined the Entrenchment of Ethics, transparence and Responsibility through the Application of ICTs in Organizations in Rivers State. In light of this, three research questions were designed to guide the study. As a descriptive driven study, 200 employees (the officials) of Stock Exchange Market in Rivers State constituted the population. From this number (200), 90 of them were randomly drawn representing 45% of the sample used for the study. Data collection was conducted using a 20- structured item of questionnaire with a modified 4-likert scale of alterative responses. Reliability test for the instrument was based on the Pearson products movement index which yielded a reliability coefficient of 0.81. All the 90 copies of questionnaire self-administered were all retrieve4, well filed and used for the study. A statistical tools of mean(x) and standard deviation(SD) were adopted as methods of data analysis. Results revealed that computers, E-mail, text message and so on are kinds of ICT tools used in promoting unethical related behaviours; that unethical behaviours/ practices can be promoted using ICTs and that ethical transparent and responsible behaviours/practices in stock exchange market are to be entrenched using ICTs. Recommended by the study are that executive managers and top officials of the stock market should encourage ethical consciousness in their respective operation branches, insist on the use of ICTs within the limit of ethical transparent and responsible parameters set out and organize conferences or seminars for all employees in the organize conferences or seminars for all employees in the organization on quarterly basis to sensitize them on the need to use ICTs in entrenching ethically transparent and responsible behaviours/practices in the organization.